(untitled) - Feldman, Robert S. (New York, 2011)
POWEp Learning is the only firstyear experience text with a unifying system for critical thinking and problem solving; POWER Learning maximizes students potential for success in college and in life; Using the scientificallybased yet simple and classtested principles of the POWER system students gain a sense of mastery and achievement as they move through the text; with the growth of their confidence comes the increased intellectual enthusiasm and personal discipline needed for them to excel.
Keywords: Study skill,Life skill,Kỹ năng học tập,Kỹ năng sống